Barriers and Solutions: International Students’ Experiences in Intercultural Communication - Peter Mduwile; Dulumoni Goswami; Didymus Ibrahim; Janeth Lufunga; Atida Mbingamno (Scientia Publica Media, 2026)
As global student mobility expands, intercultural communication (IC) has become an essential aspect of the international student experience. In multicultural countries like India, international students often face challenges related to language, culture, and academic integration. Assam, an emerging educational hub in Northeast India, remains under-researched in this context, particularly regarding how well it supports the intercultural adaptation of foreign students. This study investigates the intercultural communication challenges faced by international students in Assam and explores the coping strategies they employ. It focuses on identifying barriers across sociocultural, educational, individual, and interpersonal domains. A mixed-methods design was used. Quantitative data were collected through structured surveys from 39 students representing 25 countries. These surveys explored communication preferences, language use, and cultural adjustment difficulties. Qualitative data were gathered through in-depth interviews with four students to provide deeper insights. Data were analyzed using descriptive statistics by SPSS 27.0 version and thematic coding for the interview schedule. The study found that 51.3% of students faced IC challenges, despite some initially denying such experiences. English was the primary communication language (61.5%), but limited fluency in Hindi or Assamese hindered interaction with locals. Common issues included tone misinterpretation, gestures, and religious sensitivities. “Culture shock” was the most reported challenge (73.3%), particularly related to food, customs, and personal boundaries. Language barriers also impacted academic engagement. Students commonly responded by initiating open discussions (53.8%) or observing and analyzing situations (48.7%). The study highlights the critical role of language proficiency, cultural awareness, and adaptive strategies in improving intercultural communication. It urges institutions to promote inclusive, culturally responsive environments for international students.